2011
DOI: 10.5539/ibr.v4n3p243
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis on Negotiation Styles by Religious Beliefs

Abstract: Globalization and economic openness have contributed to increased international negotiations in the 21 st century. Despite the enthusiasm for increased global interaction and economic exchange, many people have found that cultural differences have hindered their ability to efficiently conduct business or negotiations due to their lack of understanding of the cultural differences in different countries.This paper explores the impact of religious culture on negotiations. Specifically, we compare and contrast the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 32 publications
(16 reference statements)
0
8
0
Order By: Relevance
“…Tu and Chih use the four negotiation styles of Casse and Deols, namely: factual style, normative style, intuitive style, and analytical style. The study concluded that religious culture was a significant variable that influenced the factual, normative, intuitive, and analytical negotiating styles (Tu & Chih 2011). There are similarities between Buddhists and Muslims in negotiations because both use a more normative and intuitive style, so the negotiations between the two groups experienced great success.…”
Section: Multireligion Community Cultural Negotiation and Social Learningmentioning
confidence: 98%
“…Tu and Chih use the four negotiation styles of Casse and Deols, namely: factual style, normative style, intuitive style, and analytical style. The study concluded that religious culture was a significant variable that influenced the factual, normative, intuitive, and analytical negotiating styles (Tu & Chih 2011). There are similarities between Buddhists and Muslims in negotiations because both use a more normative and intuitive style, so the negotiations between the two groups experienced great success.…”
Section: Multireligion Community Cultural Negotiation and Social Learningmentioning
confidence: 98%
“…Religious beliefs impact the behavior and decision-making of the individuals (Richardson & Rammal, 2018), and affect conflict resolutions (Blankley, 2013). When negotiators are prepared and know how religion impacts negotiation, they gain an advantage over their negotiating partners (Tu & Chih, 2011). The relationships between countries may also be affected by the history between the nations (Wolski, 2016), because history forms customs and has a very strong effect on its members (Qu, 2015).…”
Section: Language Religion and Historymentioning
confidence: 99%
“…negotiators should never assume that all citizens of particular foreign country practice the same religion or that all people practicing a particular religion uphold the same ethical standards (Blankley, 2013). Knowledge about the religion of the negotiating partner, combined with respect for their beliefs, helps develop mutual respect and trust between parties, which potentially leads to higher chances of achieving a successful negotiation (Tu & Chih, 2011). As illustrated above, there is not much surprise waiting for the U.S. negotiators in Poland.…”
Section: Us-polandmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the conceptual framework is based on Jung's (1967) psychological types (sensing VS intuition and thinking VS feeling). While Casse and Deol (1985) endeavored to distinguish between negotiating skills and styles, others have worked on assessing the context of negotiation styles through Exploratory Factor Analysis (Tu, 2007), reliability studies (Tu, 2007;Tu, 2010;Tu & Chih, 2011;, and critical ratios, reliability estimates and validation .…”
Section: Negotiation Theorymentioning
confidence: 99%